1994
DOI: 10.3109/10739689409148269
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Renal Microvascular Reactivity to Angiotensin II in Diabetic Rats

Abstract: We conclude that the blunted reactivity of afferent and efferent arterioles to Ang II among diabetic hydronephotic kidneys cannot be fully explained by the influence of renal vascular-derived dilator prostaglandins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
13
2
Order By: Relevance
“…However, the renal vasculature is also highly sensitive to the vasodilator effects of Ang 1-7, particularly at the afferent arteriole (24), and in states associated with activation of the local RAS, leading to an increase in effective renal plasma flow following an infusion of Ang 1-7 in rats (25). We demonstrate for the first time that the circulating ACE2 activity is significantly increased in diabetic mice, potentially contributing to impaired reactivity to Ang II (23). Moreover, suppression of this circulating angiotensinase activity with a selective ACE2 inhibitor was able to prevent diabetes-associated hyperfiltration.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the renal vasculature is also highly sensitive to the vasodilator effects of Ang 1-7, particularly at the afferent arteriole (24), and in states associated with activation of the local RAS, leading to an increase in effective renal plasma flow following an infusion of Ang 1-7 in rats (25). We demonstrate for the first time that the circulating ACE2 activity is significantly increased in diabetic mice, potentially contributing to impaired reactivity to Ang II (23). Moreover, suppression of this circulating angiotensinase activity with a selective ACE2 inhibitor was able to prevent diabetes-associated hyperfiltration.…”
Section: Discussionmentioning
confidence: 75%
“…Increased renal blood flow in early diabetes is thought to be due to dilation of resistance arterioles, associated with an impaired reactivity to exogenous Ang II (23). However, the renal vasculature is also highly sensitive to the vasodilator effects of Ang 1-7, particularly at the afferent arteriole (24), and in states associated with activation of the local RAS, leading to an increase in effective renal plasma flow following an infusion of Ang 1-7 in rats (25).…”
Section: Discussionmentioning
confidence: 99%
“…A second possible explanation for this finding is that hyperfiltering patients may exhibit increased renal AngII receptor density. However, this, too, is unlikely because studies have shown a downregulation in these receptors (34,35). A third possible cause is a reduced tubuloglomerular feedback signal (36).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ influx through VGCCs is also an important component of the afferent arteriolar response to numerous vasoconstrictor agonists (1,20), such that impaired Ca 2ϩ entry through this pathway could contribute to diminished agonist-induced vasoconstriction in IDDM (40)(41)(42). For example, the selective preglomerular defect in norepinephrine responsiveness in our model of IDDM (6) correlates well with the functional localization of VGCCs within the renal microvasculature (1,20), and is consistent with the postulate that a defect in VGCC activity might underlie altered norepinephrine responsiveness in IDDM.…”
Section: Discussionmentioning
confidence: 99%